(untitled) (EAAE Annual Conference Proceedings, 2025)
Modernity teaches architecture a lesson in humility and makes it occupy an integral place in the hierarchy of global values, but nevertheless one of many important links in the chain of interdependencies affecting the condition of our world. This is not a degradation, but rather an opportunity to bring it back to reality and an order; to take a self-critical look in the mirror of its historical evolution (Heynen, 2024, 100005). Never before in history to such an extent has architecture had to confront its works with such an onslaught of research from disciplines seemingly distant from it, e.g.: environmental engineering, health sciences, environmental psychology etc., as it is today. A contemporary architect must not only be a visionary, but also a social negotiator for the value of architecture. The system of architectural education, despite its efforts, has not kept pace with the scale of these challenges. The speed at which new or long-standing and neglected problems are growing indicates that the transfer of knowledge should be based on a clear message – contemporary narratives are not given once and for all or necessarily universal. They are merely the currently available output of a transhistorical process constantly updating itself against changing needs and the availability of resources. In the context of subject of the future of professional education for architects, this abstract advocates: first, adopting the formula of problem-based knowledge transfer as paramount in the course of teaching, and thus opening students to analytical approaches and new dimensions of interdisciplinarity. The introduction of a course almost identical to the title of the conference – Transhistorical Experiences, which would problematically and comparatively analyze contemporary issues against the backdrop of the chronology of past lessons already learnt and non-architectural conditions. Thirdly, the introduction of mandatory interdepartmental courses in which students from different disciplines would collaborate on a design task. Finally, to ‘de-hermetize’ architecture schools through the mandatory introduction of design courses with the authentic participation of invited social groups, as well as the mandatory courses on social communication and mediation of architecture. Heynen, Hilde. 2024. “Architectural history today: Where do we stand? Where do we go?”. Review Article. Perspectives in Architecture and Urbanism 1 (2024) 100005